PROBLEM-BASED LEARNING METHOD USE IN THE CIVIL CONSTRUCTION ORGANIZATIONAL ENVIRONMENT - Martins, Vitor William Batista; Neves, Renato Martins das; Bastos, Leonardo dos Santos Lourenço; Melo, André Cristiano Silva; Nunes, Denilson Ricardo de Lucena (Brazilian Journal of Operations & Production Management, 2016)
The changes in the civil construction context, and consequently the production management of constructions, require a different profile engineer, which demands more refined skills from those professionals, such as innovation, focus on customer, production planning and control, quality management systems knowledge, sustainability and a humanist vision. The main objective of this paper is to show the efficiency of using the Problem Based Learning methodology adapted to the organizational context. The research strategy adopted was the Research-Action, in which   the research team aimed the improvement of the way professionals understand and solve problems. The results involved the development of abilities related to the organizational context, as well as the individual, collective and organizational learning skills, highlighting problems and possible solutions for the company. Through increasing these skills, it was possible to stimulate a humanistic and sustainable vision, customer-focused, and a better quality management system. In addition, problems in this system were presented, which stated the necessity of creating an environment which enables the exchange of information among its sectors.